Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
0 votes

Using mathematical induction prove that \( \large\frac{d}{dx}\normalsize (x^{\large n}) = nx^{\large{n-1}} \) for all positive integers \(n\).

Can you answer this question?

1 Answer

0 votes
  • By using the property of mathematical induction,we prove $P(1)$- to be true $P(k)$ and $P(k+1)$ to be true when $n=1,k,k+1$.
Step 1:
Let $P(n)=\large\frac{d}{dx}$$(x^{\large n})=nx^{\large n-1}$------(1)
To verify the statement for $n=1$.
Put $n=1$ in (1) we get
Which is true as $\large\frac{d}{dx}$$(x)=1$
Suppose $P(x)$ is true for $n=m$.
$P(m)=\large\frac{d}{dx}$$(x^{\large m})=mx^{\large m-1}$
Step 2:
We establish the truth of $P(m+1)$ we prove
$P(m+1)=\large\frac{d}{dx}$$(x^{\large m+1})=(m+1)x^{\large m}$
Since $x^{\large m+1}=x^{\large 1}.x^{\large m}$
$\large\frac{d}{dx}$$(x^{\large m+1})=\large\frac{d}{dx}$$(x.x^{\large m})$
$\qquad\qquad=x\large\frac{d}{dx}$$(x^{\large m})+x^{\large m}.\large\frac{d}{dx}$$(x)$
$\qquad\qquad=x.mx^{\large m-1}+x^m.1$
$\qquad\qquad=mx^{\large m}+x^{\large m}$
$\qquad\qquad=(m+1)x^{\large m}$
$\qquad\qquad=(m+1)x^{\large (m+1)-1}$
Step 3:
$P(m+1)$ is true if $P(m)$ is true.
By principle of induction $P(n)$ is true for all $n\in N$.
answered May 15, 2013 by sreemathi.v

Related questions

Ask Question
student study plans
JEE MAIN, CBSE, AIPMT Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App